Dexmedetomidine depresses neuronal activity in the subthalamic nucleus during deep brain stimulation electrode implantation surgery - Corey Amlong; Deborah Rusy; Robert D. Sanders; Wendell Lake; Aeyal Raz (BJA Open, 2022)
Background: Micro-electrode recordings are often necessary during electrode implantation for deep brain stimulation of the subthalamic nucleus. Dexmedetomidine may be a useful sedative for these procedures, but there is limited information regarding its effect on neural activity in the subthalamic nucleus and on micro-electrode recording quality. Methods: We recorded neural activity in five patients undergoing deep brain stimulation implantation to the subthalamic nucleus. Activity was recorded after subthalamic nucleus identification while patients received dexmedetomidine sedation (loading – 1 μg kg−1 over 10–15 min, maintenance – 0.7 μg kg−1 h−1). We compared the root-mean square (RMS) and beta band (13–30 Hz) oscillation power of multi-unit activity recorded by microelectrode before, during and after recovery from dexmedetomidine sedation. RMS was normalised to values recorded in the white matter. Results: Multi-unit activity decreased during sedation in all five patients. Mean normalised RMS decreased from 2.8 (1.5) to 1.6 (1.1) during sedation (43% drop, p = 0.056). Beta band power dropped by 48.4%, but this was not significant (p = 0.15). Normalised RMS values failed to return to baseline levels during the time allocated for the study (30 min). Conclusions: In this small sample, we demonstrate that dexmedetomidine decreases neuronal firing in the subthalamic nucleus as expressed in the RMS of the multi-unit activity. As multi-unit activity is a factor in determining the subthalamic nucleus borders during micro-electrode recordings, dexmedetomidine should be used with caution for sedation during these procedures. Clinical trial number: NCT01721460.